2009
DOI: 10.3748/wjg.15.5838
|View full text |Cite
|
Sign up to set email alerts
|

Image-guided conservative management of right colonicdiverticulitis

Abstract: AIM:To study the clinical outcomes of medical therapy in patients with right colonic diverticulitis. METHODS:The records of 189 patients with right colonic diverticulitis which was finally diagnosed by computed tomography, ultrasonography, or operative findings were retrospectively reviewed. RESULTS:Of the 189 patients hospitalized for right colonic diverticulitis, the stages of diverticulitis by a modified Hinchey classification were 26 patients (13.8%) in stage 0, 139 patients (73.5%) in stage Ⅰ a, 23 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…These findings corroborate previous smaller studies that advocated non-surgical treatment for patients with right colonic diverticulitis (4,18,19). The uncomplicated disease course in these patients is similar to that of stage Ia of left colonic diverticulitis (20,21).…”
Section: Discussionsupporting
confidence: 90%
“…These findings corroborate previous smaller studies that advocated non-surgical treatment for patients with right colonic diverticulitis (4,18,19). The uncomplicated disease course in these patients is similar to that of stage Ia of left colonic diverticulitis (20,21).…”
Section: Discussionsupporting
confidence: 90%
“…Successful results of non-operative management of uncomplicated RCD in both Western and Asian patients have been published before [6,12,14,24,[28][29][30][31]37,40]. All but one of our RCD patients received antibiotics as part of their conservative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the mild disease course of RCD demonstrated by this study and the good results of non-operative, and even non-antibiotic, therapy found in recent Asian studies, it seems justified to use the same diagnostic and treatment guideline for both left-and right-sided diverticulitis. Imaging also allows clinicians to determine the optimal management according to the severity of the diverticulitis [40]. This policy will definitively shift RCD from a surgical diagnosis to a radiological diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of diverticular disease on Western society is substantial, affecting 50% of those older than 60 years, and up to 80% of those aged 80 years and older 5. Diverticular disease is predominant in the left colon in Western populations, whereas it is much more common in the right colon in Asians 3–6. Of those with diverticular disease, 10–25% will develop diverticulitis 7…”
Section: Discussionmentioning
confidence: 99%